L-Carnitine Supplementation Descreases Hepatic Triglyceride Accumulation in Holstein Cows During the Transition Period (2019)
ABSTRACT: The increased use of body reserves observed during peripartum leads to higher needs of L-carnitine by cows, which is restrictive under the production conditions of Colombian high tropics. Objective: To evaluate the lipotropic potential of L-carnitine in Holstein dairy cows during the transition period to lactation. Methods: Twenty-one Holstein cows were fed 0, 100, or 200 g/d L-carnitine fumarate from d 260 of gestation to d 20 postpartum. Hepatic triacylglycerides concentration, total carnitine, free carnitine, acylcarnitine, and serum levels of non-esterified fatty acids (NEFA), β-hydroxybutyrate (β-HB) and urea were determined by spectrophotometry. Repeated measures analysis was used to determine the effects of dose, measurement period, and their interactions. Results: Hepatic triglycerides and the different forms of carnitine showed no difference between sampling periods (p>0.05). Hepatic triglycerides concentration was low and decreased in response to 200 g/d L-carnitine fumarate supplementation (p<0.05). This decrease in hepatic triglycerides could be due to increased fatty acid oxidation. L-carnitine supplementation significantly increased (p<0.05) blood urea concentration, possibly through stimulation of the urea cycle, as previously described in other species. Conclusion: Supplementation with L-carnitine decreased the hepatic concentration of triglycerides, possibly due to increased liver oxidation of fatty acids.